2017
DOI: 10.1160/th16-11-0825
|View full text |Cite
|
Sign up to set email alerts
|

Are cardiovascular risk factors also associated with the incidence of atrial fibrillation?

Abstract: SummaryEstablished primary prevention strategies of cardiovascular diseases are based on understanding of risk factors, but whether the same risk factors are associated with atrial fibrillation (AF) remains unclear. We conducted a systematic review and field synopsis of the associations of 23 cardiovascular risk factors and incident AF, which included 84 reports based on 28 consented and four electronic health record cohorts of 20,420,175 participants and 576,602 AF events. We identified 3-19 reports per risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(67 citation statements)
references
References 112 publications
(220 reference statements)
5
58
0
4
Order By: Relevance
“…16 Similarly, in an ancillary study from the ROCKET AF trial (rivaroxaban versus warfarin), the risk of stroke or systemic embolism increased by 7% for every 10 mm Hg increase in screening SBP. 2,18 The ARISTOTLE trial (apixaban versus warfarin) also confirmed the importance of good BP control in AF. Elevated BP at any time during the trial increased risk of stroke and systemic embolism (HR, 1.53; 95% CI, 1.25-1.86), hemorrhagic stroke (HR, 1.85; 95% CI, 1.26-2.72), and ischemic stroke (HR, 1.50; 95% CI, 1.18-1.90).…”
Section: Balancing Stroke and Bleeding Risk In Hypertension And Afmentioning
confidence: 92%
See 2 more Smart Citations
“…16 Similarly, in an ancillary study from the ROCKET AF trial (rivaroxaban versus warfarin), the risk of stroke or systemic embolism increased by 7% for every 10 mm Hg increase in screening SBP. 2,18 The ARISTOTLE trial (apixaban versus warfarin) also confirmed the importance of good BP control in AF. Elevated BP at any time during the trial increased risk of stroke and systemic embolism (HR, 1.53; 95% CI, 1.25-1.86), hemorrhagic stroke (HR, 1.85; 95% CI, 1.26-2.72), and ischemic stroke (HR, 1.50; 95% CI, 1.18-1.90).…”
Section: Balancing Stroke and Bleeding Risk In Hypertension And Afmentioning
confidence: 92%
“…79,80 Similarly, increasing body mass index is related to increased risk of AF. 2 Interventions to reduce body weight have numerous positive health effects in AF patients, including BP reduction, decrease in glucose, total cholesterol, low-density cholesterol, and triglycerides, inhibition of inflammation (eg, reduction in C-reactive protein levels), attenuation of pathological LA remodeling (ie, decrease in LA volume) and LV remodeling (reduction of LV hypertrophy and E/eʹ ratio). The most prominent effects were seen in patients with ≥10% weight reduction.…”
Section: Impact Of Physical Activity and Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…19 Dyslipidemia Dyslipidemia and the risk of atrial fibrillation Available studies showed inconsistent findings on association between dyslipidemia and incident AF. 59 The ARIC (Atherosclerosis Risk in Communities) study suggested a protective effect of hypercholesterolemia against AF, reporting a significant reduction of the 20-year incident AF risk by 12% and 16% among participants with baseline total cholesterol and low -density lipoprotein cholesterol level above 5.18 mmol/l and 2.59 mmol/l, respectively, compared with those who had lower plasma lipid levels. 60 Several studies presented discordant results on the impact of high -density lipoprotein cholesterol level on new -onset AF.…”
Section: 51mentioning
confidence: 99%
“…É verificável por exames como eletrocardiograma, ecocardiograma e ressonância magnética (SANTOS, SHAH, 2014). Nota-se que a HAS está frequentemente associada às alterações funcionais e estruturais, como a hipertrofia e fibrose miocárdicas, que desenvolvem a FA (HEERINGA et al, 2006;ALLAN, et al, 2017).…”
Section: A Hipertensão Arterial E a Fibrilação Atrialunclassified